9. NEXT GENERATION SEQUENCING REVEALED THE GENETIC LANDSCAPE OF DISEASE-ASSOCIATED VARIANTS OF PHENYLKETONURIA (Vietnam Journal of Community Medicine, 2023)
Phenylketonuria (PKU) is an autosomal recessive disorder caused by the PAH gene located onchromosome 12. The disease is characterized by a defect in the enzyme phenylalanine hydroxylase(PAH), causing elevated levels of phenylalanine (Phe) in the blood and subsequently leading toneurotoxicity and mental disability. The world prevalence of PKU was about 1 in 10,000 - 20,000newborns, still, data about PKU carriers and the disease-associated variant spectra in Vietnamesepeople is minimal. The advent of Next Generation Sequencing (NGS) allows the simultaneousdetection of multiple genetic variants, including novel variants in numerous patients within a singletest, substantially reducing the testing cost. Objectives: Our study aimed to screen the carrierfrequency of the PAH gene and uncover variant spectra of this disease in Vietnamese women.Methods: 2937 women who came for a prenatal routine healthcare check at the Center of ClinicalGenetics and Genomics - Ha Noi Medical University Hospital and Gene Solutions were screenedfor disease-associated variants of the PAH gene employing NGS. Results: Of 2937 participants,70 women were carriers (2.4%), and 12 different disease-associated variants were detected: R408Q(1/2937), V388M (2/2937), P314T (2/2937), E280K (1/2937), R241fs (1/2937), R241C (1/2937),Y206* (1/2937), Y204C (1/2937), Q172H (56/2937), H170Q (2/2937), R111* (1/2937), L41F(1/2937). Q172H was predominant in our study. There are two rare variants that allele frequencyhas not been reported in ClinVar and Ensemble: L41F và R241fs. Conclusion: The data from ourresearch will inform policymakers in constructing cost-effective genetic metabolic carrier screeningprograms.
Keywords: Phenylketonuria (PKU), variant, carriers screening, Next Generation Sequencing.